(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Since ancient times, the art of painting in Assam has evolved around the culture of adorning manuscripts with lines and colors. In other words, painting as an art form is a unique and significant resource of the Assamese cultural legacy. Since the turn of the 21st century, artists from Assam have absorbed and become acclimated to modern art practices such as installation art, performance art, and modern graffiti. My goals are to research art and artists in Assam who use a variety of methods and materials, particularly in relation to a regional context and new art genres in the midst of globalization, a complex socio-political landscape, and a zero-market for works of art and art connoisseurs.